Contribution of anisotropy of magnetic susceptibility (AMS) to reconstruct flooding characteristics of a 4220 BP tsunami from a thick unconsolidated structureless deposit (Banda Aceh, Sumatra) - Wassmer, Patrick C.; Gomez, Christopher A.; Iskandasyah, T. Yan W.M.; Lavigne, Franck; Sartohadi, Junun (Frontiers in Earth Science, 2015)
One of the main concerns of deciphering tsunami sedimentary records along seashore is to link the emplaced layers with marine high energy events. Based on a combination of morphologic features, sedimentary figures, grain size characteristics, fossils content, microfossils assemblages, geochemical elements, heavy minerals presence; it is, in principle, possible to relate the sedimentary record to a tsunami event. However, experience shows that sometimes, in reason of a lack of any visible sedimentary features, it is hard to decide between a storm and a tsunami origin. To solve this issue, the authors have used the Anisotropy of Magnetic Susceptibility (AMS) to evidence the sediment fabric. The validity of the method for reconstructing flow direction has been proved when applied on sediments in the aftermath of a tsunami event, for which the behaviour was well documented (2004 IOT). We present herein an application of this method for a 56 cm thick paleo-deposit dated 4220 BP laying under the soil covered by the 2004 IOT, SE of Banda Aceh, North Sumatra. We analysed this homogenous deposit, lacking of any visible structure, using methods of classic sedimentology to confirm the occurrence of a high energy event. We then applied AMS technique that allowed the reconstruction of flow characteristics during sediment emplacement. We show that all the sequence was emplaced by uprush phases and that the local topography played a role on the re-orientation of a part of the uprush flow, creating strong reverse current. This particular behaviour was reported by eyewitnesses during the 2004 IOT event.